2018
DOI: 10.1159/000489131
|View full text |Cite
|
Sign up to set email alerts
|

The Warwick Experience of the Oncotype DX® Breast Recurrence Score® Assay as a Predictor of Chemotherapy Administration

Abstract: Introduction: Oncotype DX® analyses the expression of 21 genes within tumour tissue to determine a Recurrence Score® (RS). RS is a marker of risk for distant recurrence in oestrogen receptor-positive early breast cancer, allowing patient-specific benefit of chemotherapy to be evaluated. Our aim was to determine whether the introduction of Oncotype DX led to a net reduction in chemotherapy use. Methods: Consecutive patients that underwent Oncotype DX at Warwick Hospital were reviewed. Patients were anonymised a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In a study from Australia that included 235 patients with LN– BC, ACT was recommended to 89 patients, but only to 37 of them when the results of ODX assay were considered indicating treatment de-escalation in 58% of patients [22]. A study from the UK reported that 43% patients were spared chemotherapy when the results of the ODX assay were considered [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study from Australia that included 235 patients with LN– BC, ACT was recommended to 89 patients, but only to 37 of them when the results of ODX assay were considered indicating treatment de-escalation in 58% of patients [22]. A study from the UK reported that 43% patients were spared chemotherapy when the results of the ODX assay were considered [23].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the value of ODX assay was investigated prospectively in the TAILOR-X trial. Patients with midrange RS (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) were randomly assigned to receive either chemo-endocrine therapy or endocrine therapy alone. Results showed that ACT did not improve the outcome of these patients [6].…”
Section: Introductionmentioning
confidence: 99%
“…Oncotype DX is a widely-used prognostic assay for the ERpositive breast cancers [85,86]. This assay utilizes the expression patterns of 16 cancer-associated genes and 5 house-keeping genes to evaluate the possibilities of a breast cancer to grow and to respond to the chemotherapeutic treatments.…”
Section: F Comparison With the Existing Gene Panels For Breast Cancersmentioning
confidence: 99%
“…It accounts for 15% of all newly diagnosed cancers and also is considered to be the most common female cancer. Up to 80% of these cases are categorized as early breast cancer [1,2].…”
Section: Introductionmentioning
confidence: 99%